Combined Mueller and Jones matrix method for the evaluation of the complex modulation in a liquid-crystal-on-silicon display - Moreno, I. (2008)
We apply the polar decomposition of the Mueller matrix describing a liquid-crystal-on-silicon display to identify the diattenuator, depolarizer, and retarder contributions as a function of the gray level. The retarder contribution is expressed in terms of the equivalent Jones matrix to apply previous techniques to evaluate the phase modulation. This allows searching for optimized polarization configurations for phase- or amplitude-only modulation responses. We present results for =633 nm showing a phase-only modulation up to 2 rad and flat intensity modulation.